Cutaneous sensory and autonomic denervation in CADASIL. (15th March 2016) - Nolano, Maria; Provitera, Vincenzo; Donadio, Vincenzo; Caporaso, Giuseppe; Stancanelli, Annamaria; Califano, Francesca; Pianese, Luigi; Liguori, Rocco; Santoro, Lucio; Ragno, Michele
Abstract : Objective: To assess the involvement of the peripheral nervous system in cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) by means of immunofluorescence and confocal analysis of punch skin biopsies. Methods: We recruited 14 unrelated patients with CADASIL (M/F = 9/5; age 53.9 ± 10.5 years) and 52 healthy controls (M/F = 31/21; age 53.8 ± 9.8). Patients underwent clinical and neuroradiologic assessment. Three-millimeter punch skin biopsies were taken from the fingertip, the thigh, and the distal leg and processed using indirect immunofluorescence and a panel of primary antibodies to mark vessels and sensory and autonomic nerve fibers. Intraepidermal nerve fibers (IENF), Meissner corpuscles (MC), and sudomotor, vasomotor, and pilomotor nerves were assessed using confocal microscopy. Results: In patients, compared to controls, we found a severe loss of IENF at the distal leg ( p < 0.01), at the thigh ( p < 0.01), and at the fingertip ( p < 0.01) with a non-length-dependent pattern and a loss of MC ( p < 0.01). A severe sudomotor, vasomotor, and pilomotor nerve fiber loss was found by semiquantitative evaluation. Along with nerve loss, a severe derangement of the vascular bed was observed. In our patient population, sensory and autonomic denervation did not correlate with age, sex, type of mutation, or MRI involvement. Conclusions: We found an involvement of the peripheral nervous system in patients with CADASIL through the assessment of cutaneous somatic and autonomic nerves. The neurovascular derangement observed in the skin may reflect, although to a lesser extent, what happens in the CNS.